PREPARATION OF FUTURE TUTORS OF PRESCHOOL CHILDREN IN THE CONTEXT OF MODERN EDUCATIONAL PARADIGMS - Palamar, Svitlana; Naumenko, Maryna (Educological discourse, 2020)
The article identifies the impact of changing of educational paradigms on the organization of the educational process in the institutions of higher education of Ukraine, in terms of its integration into the European educational space. Modern researches on a certain topic are analyzed, taking this into account, it was found out that the quality of the educational process in a higher education institution (HEI) is determined by a specialist (graduate of HEI), who possesses a high level knowledge in a certain domain, is able to use and actively uses this knowledge in the practice of his activity, has the developed competences and skills in accordance with the chosen profession, is competent and competitive in the world labor market. The analyzed results of the World Bank's research on “Skills for Contemporary Ukraine” (2015) have shown that cognitive skills, self-organization, resilience, teamwork and the desire to learn are relevant, and that by 2030, professionals with critical thinking and a project-based approach to solving problems will succeed. The stages of formation of educational paradigms, the formation of which took place over a long historical period, outlining the stability of the development of pedagogical science, are analyzed. The modern educational paradigms are reviewed and their classification is presented (by T. Popova). It was established that the essence of the humanistic paradigm in the educational process, built on a personality-oriented approach, meets the needs of students, with their inherent modern values and interaction of participants in the educational process. In the context of the humanistic paradigm, the modern educator must strive for self-improvement and promote self-development and self-education; successfully combine theoretical knowledge and practical skills; use the experience of traditional and evidence-based pedagogy; be aware of modern preschool education, know and apply modern technologies, methods and actively implement own pedagogical achievements in practice; be effective and critical in accordance with the situation; have an objective self-assessment. The factors influencing the quality of vocational training of future preschool tutors were determined according to the results of a survey of 4-5 pre-school students of the specialty “Preschool Education” of the Borys Grinchenko Kyiv University.